2022
DOI: 10.1007/s40475-022-00262-9
|View full text |Cite
|
Sign up to set email alerts
|

Nervous System Manifestations of Arboviral Infections

Abstract: Purpose of Review Complex environmental factors and human intervention influence the spread of arthropod vectors and the cycle of transmission of arboviruses. The spectrum of clinical manifestations is diverse, ranging from serious presentations like viral hemorrhagic fever (e.g., dengue, yellow fever, rift valley fever) or shock syndromes (e.g., dengue virus) to organ-specific illness like meningoencephalitis. Recent Findings A spectrum of clinical neurologic syndromes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 136 publications
(89 reference statements)
1
4
0
Order By: Relevance
“…Based on relevant historical, laboratory, and imaging features a comprehensive investigation to include Epstein-Barr virus, enterovirus, lymphocytic choriomeningitis, listeria monocytogenes, mycobacteria, fungal, rickettsial and parasitic infections, along with noninfectious mimics as autoimmune encephalitidies and various demyelinating conditions, is warranted. 10 MR changes noted in the thoracic spinal cord are consistent with motor neuron involvement as demonstrated with POWV infection involvement in spinal cord ventral horn in a mouse model 11 and as described with other arboviruses. 9 Considering the variable clinical and imaging features both within and among geographic regions, question remains whether the vector or its effect on the virus has a role in determining how Powassan presents, given differing region vectors (Ixodes scapularis vs. Ixodes cookie).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Based on relevant historical, laboratory, and imaging features a comprehensive investigation to include Epstein-Barr virus, enterovirus, lymphocytic choriomeningitis, listeria monocytogenes, mycobacteria, fungal, rickettsial and parasitic infections, along with noninfectious mimics as autoimmune encephalitidies and various demyelinating conditions, is warranted. 10 MR changes noted in the thoracic spinal cord are consistent with motor neuron involvement as demonstrated with POWV infection involvement in spinal cord ventral horn in a mouse model 11 and as described with other arboviruses. 9 Considering the variable clinical and imaging features both within and among geographic regions, question remains whether the vector or its effect on the virus has a role in determining how Powassan presents, given differing region vectors (Ixodes scapularis vs. Ixodes cookie).…”
Section: Discussionsupporting
confidence: 81%
“…Other conditions that may manifest similar prominent cerebellar imaging abnormality can include other viral, inflammatory, infectious, and neoplastic causes. Based on relevant historical, laboratory, and imaging features a comprehensive investigation to include Epstein-Barr virus, enterovirus, lymphocytic choriomeningitis, listeria monocytogenes, mycobacteria, fungal, rickettsial and parasitic infections, along with noninfectious mimics as autoimmune encephalitidies and various demyelinating conditions, is warranted 10 …”
Section: Discussionmentioning
confidence: 99%
“…Arbovirus selection was determined based on the experience of authors residing in endemic zones in addition to the recently established scientific literature on emerging arboviruses. 6 The following search terms were utilized: “Neuroinvasion arboviruses,” “neurotropic arboviruses,” “neurovirulent arboviruses,” “West Nile neuroinvasive disease,” “Zika virus,” “congenital Zika syndrome,” “Chikungunya virus,” “Dengue virus,” “Tick-borne encephalitis virus,” “St. Louis encephalitis virus,” “Japanese encephalitis virus,” “Powassan virus,” “Mayaro virus,” “Yellow fever virus,” and “Rift valley fever virus,” “Eastern Equine encephalitis virus.” When appropriate Boolean operators such as “AND”/“OR,” and the wildcard “*” were used within and between search terms.…”
Section: Methodsmentioning
confidence: 99%
“…Other viral causes should be investigated in selected cases, depending on the epidemic context, geographic region, season, and in immunocompromised and/or unvaccinated patients. Rare causes such as anthrax meningoencephalitis [20], tick-borne encephalitis [21][22][23], and arboviruses [24] have been described in the adult population, highlighting the need to look for a specific clinical context in cases of severe meningoencephalitis of unknown origin. A recent retrospective review found that large CSF serologic panels (i.e.…”
Section: Bacterial Causesmentioning
confidence: 99%